Saliva Cortisol in Girls With Functional Abdominal Pain Disorders: A Randomized Controlled Dance and Yoga Intervention - Elin Areskoug Sandberg; Elin Areskoug Sandberg; Anna Duberg; Ulrika Lorenzon Fagerberg; Ulrika Lorenzon Fagerberg; Evalotte Mörelius; Evalotte Mörelius; Stefan Särnblad (Frontiers Media S.A., 2022)
IntroductionFunctional abdominal pain disorders (FAPDs) are common among girls and has been associated with stress. Cortisol is one of the major stress hormones. Dance and yoga have been shown to reduce abdominal pain among girls with FAPDs.AimTo investigate the effect of an 8-month intervention with dance and yoga on cortisol levels in saliva among girls with FAPDs.MethodsA total of 121 girls aged 9-13 years with irritable bowel syndrome (IBS) or functional abdominal pain were included in the study. Participants were randomized into an intervention group and a control group. The intervention group attended a combined dance and yoga session twice a week for 8 months. Saliva samples were collected during 1 day, in the morning and evening, at baseline, and at 4 and 8 months. Subjective pain and stress were assessed as well.ResultsNo significant effects on saliva cortisol levels between groups were observed after completion of the intervention at 8 months. However, evening cortisol and evening/morning quotient were significantly reduced at 4 months in the intervention group compared to the control group (p = 0.01, p = 0.004). There was no association between cortisol quota and pain or stress.ConclusionImprovements in cortisol levels were seen in the intervention group at 4 months but did not persist until the end of the study. This indicates that dance and yoga could have a stress-reducing effect during the ongoing intervention.